THE CYLINDRICAL ABDOMINOPERINEAL RESECTION: SHORT-TERM RESULTS AND OUTSTANDING ISSUES - M. A. Chernichenko; A. V. Boyko; D. V. Sidorov; L. O. Petrov (Исследования и практика в медицине)
Abstract:Objective. Analysis of short-term outcomes patients with low rectal cancer after cylindrical abdominoperineal resection.Materials and methods. This study enrolled 20 patients with locally advanced low rectal cancer who underwent preoperative chemoradiotherapy and surgery or surgery alone after using the technique of CAPE.Results. Analysis of short-term outcomes after CAPE showed a high frequency of postoperative complications, especially in group of patients who underwent preoperative chemoradiotherapy. On the one hand it dictates need for careful patient selection for this type of operation, and on the other hand encourages us to improve the technique of operations.Conclusions. The cylindrical abdominoperineal resection allows to achieve good local control in patients with locally advanced low rectal cancer.